Recent advances in the management of knee osteoarthritis: a narrative review - Shtroblia, Viktor; Petakh, Pavlo; Kamyshna, Iryna; Halabitska, Iryna; Kamyshnyi, Oleksandr (Frontiers in Medicine, 2025)
Knee osteoarthritis (OA) is a common condition that causes pain and reduces the quality of life for many people. It also leads to high health and financial costs. Managing knee OA pain requires using different methods together for the best results. This review overviews current therapeutic options for knee OA pain, focusing on their efficacy, safety, and potential roles in clinical practice. Topical treatments, such as NSAIDs and capsaicin, offer significant pain relief with minimal systemic side effects and are suitable for initial therapy, together with nonpharmacologic interventions like exercise and, when relevant, weight loss. Oral analgesics, including acetaminophen and opioids, have limited efficacy and serious side effects, making them appropriate only for short-term or rescue therapy. Intra-articular injections, such as corticosteroids, hyaluronic acid, and platelet rich plasma, demonstrate varying levels of efficacy and safety. Nutritional supplements, including curcumin, Boswellia serrata, and glucosaminechondroitin combinations, offer modest benefits and are best used as adjuncts to standart treatment. Nonpharmacological treatments, such as transcutaneous electrical nerve stimulation (TENS), acupuncture, and local heat therapy, provide variable pain relief and should be customized based on individual patient responses. Targeted biologic agents, such as antibodies to TNF-α, IL-1, and NGF, hold promise for more precise pain relief; however, further research is required to establish their routine use. Treating knee OA pain should be personalized, combining several methods. Research must continue to improve treatments and make them safer.